Opportunities for high-energy neutron- and deuteron-induced measurements for fusion technology at the Soreq applied research accelerator facility (SARAF) - Mardor, I.; Wilsenach, H.; Dickel, T.; Eliyahu, I.; Friedman, M.; Hirsh, T. Y.; Kreisel, A.; Sharon, O.; Tessler, M.; Vaintraub, S.; Uhlemann, F. V. (Frontiers in Physics, 2023)
The Soreq Applied Research Accelerator Facility (SARAF) will be based on a 40 MeV, 5 mA CW (continuous wave) proton/deuteron superconducting linear accelerator, currently under construction at Soreq Nuclear Research Center in Yavne, Israel. It is planned to commence operation during 2025. Experiments at SARAF could provide data on high-energy deuteron-and neutron-induced crosssections, yields and radiation damage, which are invaluable for the design and operation of the International Fusion Materials Irradiation Facility-DEMO-Oriented NEutron Source (IFMIF-DONES), and fusion technology in general. Pulsed beams (~1 nsec) of variable energy deuterons will irradiate a lithium target and generate pulsed neutron beams with energy up to ~55 MeV, which will be used to measure energy-dependent neutron-induced differential cross-sections, utilizing time of flight techniques. Impinging continuous wave (CW) 40 MeV deuteron beams on a unique galliumindium (GaIn) liquid-jet target, will generate a neutron rate of more than 1×10 15 n/sec, with energies up to ~45 MeV. We plan to use this high rate to measure integral neutron-induced reaction yields of all channels simultaneously, employing an original novel method that will identify the reactionproduced nuclei via accurate mass measurement. The neutron-energy dependence of the yields could be deduced by combining measurements at various deuteron energies. The measured cross-sections and yields at SARAF may predict the activation characteristics of construction materials of IFMIF-DONES and future fusion reactors. The deuteron beams will also be used directly to measure crosssections via in-beam and offline methods. The high neutron and deuteron rates will extend SARAF's reach to rare materials. The deuteron beam power density on the liquid GaIn target will be 100 kW/cm 2 (similar to IFMIF-DONES) on a 2 cm 2 spot. The resulting neutron flux on small secondary samples will be in the 10 13 n/cm 2 /s level, only an order of magnitude less than IFMIF-DONES. Therefore, SARAF may serve as a pilot facility for fusion-related radiation damage studies, providing important information towards the design of IFMIF-DONES.